Bibliographic survey on the association of rhizobia and arbuscular mycorrhizal fungi in Vigna unguiculata L. Walp. (cowpea bean) (Research, Society and Development, 2022)
Legumes are easily identifiable plants due to the type of their fruits (legumes), which are produced in the form of a pod. Cowpea is an example of these legumes, widely cultivated and consumed on a large scale. Plants of the legume group also stand out for the important biological fixation of atmospheric nitrogen, with the help of microorganisms, such as rhizobia and mycorrhiza. The objective was to review in the literature publications that tested the effectiveness of microorganisms in the growth of cowpea (Vigna unguiculata L. Walp.). The study was developed through a theoretical approach, in which researches were carried out on works published in the Scientific Electronic Library Online – SciELO and U.S. databases. National Library of Medicine – PubMed, Google Scholar search engine and specialist websites. Works with experimental approach studies conducted in a greenhouse and in the field were included. Agronomic efficiency of cowpea was evaluated when inoculated with the strains BR3299, BR3262, UFLA03-164, BR3267, INPA03 -11B and with the mycorrhizal fungi species Scutellospora heterogama, Glomus margarita, Rhizophagus clarus and Claroideoglomus etunicatum. The rhizobia strains INPA03-11B and BR3262 showed to be more efficient for cowpea inoculation, while the fungus efficiency was according to the soil to be used.